2017
DOI: 10.3844/ajisp.2017.45.49
|View full text |Cite
|
Sign up to set email alerts
|

Glucans and the Poultry Immune System

Abstract: Abstract:With the reduced availability of antibiotics, poultry producers are looking for feed additives to stimulate the immune system of their birds. Some beta-glucans have been shown to improve gut health in poultry subjected to a bacterial challenge, to increase the flow of new immunocytes into the various lymphoid organs, to increase macrophage function, to increase antibody titers after a vaccination and to function as an anti-inflammatory immunomodulator. As a result, beta-glucans may provide a tool for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
0
27
1
Order By: Relevance
“…Although, Zhang et al [22] study showed that there were no differences in RBC, WBC, lymphocyte in broilers fed β-glucan, Petravić-Tomenac et al [23] and Jacob and Pescatore [6] reported that an activation of WBCs such as macrophages, granulocytes and monocytes was observed in chickens fed β-glucan; In the present study, WBCs and lymphocyte also increased with 1,3-1,6 β-glucan in diet. These cells are responsible for defense against infection and support the repair of damaged tissues in the body.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Although, Zhang et al [22] study showed that there were no differences in RBC, WBC, lymphocyte in broilers fed β-glucan, Petravić-Tomenac et al [23] and Jacob and Pescatore [6] reported that an activation of WBCs such as macrophages, granulocytes and monocytes was observed in chickens fed β-glucan; In the present study, WBCs and lymphocyte also increased with 1,3-1,6 β-glucan in diet. These cells are responsible for defense against infection and support the repair of damaged tissues in the body.…”
Section: Discussioncontrasting
confidence: 59%
“…β-Glucans have drawn ever-increasing attention thanks to their innate immune system immunomodulatory properties [6]. The 1,3-1,6 β-glucan present in YCW should be recognized as an immune modulator substance in animals and humans [7]; thus, dietary YCW might exert some benefits on the immune system of intestinal mucosa [8].…”
Section: Introductionmentioning
confidence: 99%
“…Protecting animal companions from maladies is an improvement to the overall public health of society, both by reducing health care costs for animals and by decreasing the incidence of zoonotic disease transmission as is the case with rabies (67). The use of such public health measures could also serve as an alternative to antibiotic use to protect production animals against infectious diseases (68, 69). Furthermore, vaccines that can provide early and broad protection via trained immunity would greatly benefit the agricultural industry, where for instance many chicks, piglets and calves are lost each year due to the inefficacy of many vaccines in very early life.…”
Section: Resultsmentioning
confidence: 99%
“…Proinflammation cytokines (TNF-α, interferon gamma, and IL-1) are the basic proteins of immunity and have been considered as endogenous signal molecules that mediate the cellular defense system against inflammatory response induced by high ambient temperature ( Hietbrink et al., 2006 ). Meanwhile, IL-1, interferon gamma, and TNF-α may serve as signals to enhance the immune response, including activating cytotoxic macrophages, T-helper and natural killer cells, as well as promotion T cell proliferation and differentiation ( Jacob and Pescatore., 2017 ). In agreement with our results, the increased levels of proinflammation cytokines of heat-exposed birds have been documented by previous works ( Chang, 1993 ; Camus et al., 1998 ; Ostrowski et al., 1998 ; Moldoveanu et al., 2000 ; Suzuki K., 2000 ).…”
Section: Discussionmentioning
confidence: 99%